FLUTUAÇÃO POPULACIONAL E ANÁLISE FAUNÍSTICA DE CARABIDAE E STAPHYLINIDAE (COLEOPTERA) EM JABOTICABAL, SÃO PAULO - Cividanes, F.j. [UNESP]; Cividanes, T.m.s. (Instituto Biológico, 2022)
In this study a population survey of Carabidae and Staphylinidae (Coleoptera) adults was carried out with the aim to analyze their populations through faunistic indexes and to determine the influence of temperature, relative humidity and rainfall. The study was conducted in two areas cultivated with soybean/corn under no-tillage and conventional tillage systems and adjacent to a forest fragment and a Pinus stand, respectively. Beetles were sampled by pitfall traps distributed in two 100-m transects. The fauna was characterized by diversity (H), evenness (J), abundance, dominance, frequency and constancy indexes. The influence of air temperature, relative humidity and rainfall was verified using stepwise regression. The carabids Abaris basistriatus Chaudoir, Odontochila nodicornis (Dejean) and Scarites sp. were classified as predominant species in both areas, while Selenophorus alternans Dejean only classified as predominant in the area underconventional tillage system, likewise for Megacephala sp. and Selenophorus seriatoporus Putz. in the no-tillage area. The predominant species showed just onepopulation peak eachyear, usually observed from December to January. The pluvial precipitation influenced the occurrence of the carabids positively and significantly, with O. nodicornis and Megacephala sp. being the most demanding species in relation to the effect of humidity on their dispersal.

No presente estudo efetuou-se um levantamento populacional de adultos de Carabidae e Staphylinidae (Coleoptera) visando-se analisar suas populações por meio de índices faunísticos e determinar a influência da temperatura, umidade relativa e precipitação pluvial. O estudo foi realizado em duas áreas com culturas de soja/milho cultivadas em sistemas de plantio direto e convencional adjacentes a fragmento florestal e povoamento de Pinus, respectivamente. Os besouros foram amostrados por meio de armadilhas de solo distribuídas em dois transectos de 100 m de comprimento. A partir dos dados de riqueza e abundância foram calculados índices de diversidade (H), equitabilidade (J), abundância, dominância, freqüência e constância. A influência da temperatura do ar, umidade relativa e precipitação pluvial na ocorrência destes besouros foi analisada por regressão múltipla com seleção de variáveis pelo método stepwise. Os carabídeos Abaris basistriatus Chaudoir, Odontochila nodicornis (Dejean) e Scarites sp. foram dominantes nas duas áreas estudadas. Já Selenophorus alternans Dejean, apenas na área sob sistema de plantio convencional enquanto Megacephala sp. e Selenophorus seriatoporusPutz., em sistema de plantio direto. As espécies dominantes apresentaram apenas um pico populacional por ano, ocorrendo geralmente de dezembro a janeiro. A precipitação pluvial influiu positiva e significativamente na ocorrência de carabídeos com O. nodicornis e Megacephala sp. sendo os mais exigentes quanto à umidade para se dispersarem.
FAUNISTIC ANALYSIS AND POPULATIONAL FLUCTUATION OF CARABIDAE AND STAPHYLINIDAE (COLEOPTERA) IN JABOTICABAL, STATE OF SÃO PAULO, BRAZIL
Keywords: Biological control; Glycine max; Pinus; weather; Zea mays; Controle biológico; condições meteorológicas; Glycine max; Pinus; Zea mays